Behavior of large-scale bracing system in tall buildings subjected to earthquake loads - Hemmati, Ali; Kheyroddin, Ali (Journal of Civil Engineering and Management, 2013)
Bracing is a highly efficient and economical method of resisting of lateral forces in a steel structure. The most common types of bracing are those that form a fully triangulated vertical truss. These include the concentric and eccentric braced types. In high-rise buildings, the location and number of bracings is an important limitation to the architectural plan. A similar scheme has been used in larger scale spanning multiple stories and bays in tall buildings which is called large-scale bracing system. Large-scale bracing (LSB) is a particular form of a space truss. It consists of multiple diagonal elements that form a diagonal grid on the face of the structure. In this paper, a 20 story steel frame with different arrangement of bracing systems is analyzed. Linear and static nonlinear (push-over) analyses are carried out and the results presented here. Analytical results show that, the large-scale bracing is more adequate system under the lateral loads. Using LSB in tall buildings, decreases the lateral displacement, drift ratio, uplift forces in foundation and increases the ductility and shear absorption percent of the bracing system. Moreover, the stress ratios in the structural members of LSB system are less than the relevant values in other bracing systems.